Three Million Foreigners, Three Million Unemployed? : Immigration and the French Labor Market - Gross, Dominique (IMF Working Papers; Working Paper, 1999)
This paper investigates the effects of the flows of immigrant workers on the French labor market between the mid-1970s and mid-1990s. Using a system of equations for unemployment, labor-force participation, the real wage, and the immigration rate, it is shown that, in the long run, legal and amnestied immigrant workers, and their families, lower the unemployment rate permanently. In the short run, the arrival of immigrants increases unemployment slightly with an impact similar to that of an increase in domestic labor-force participation. The composition of immigration flows matters, and the proportion of skilled and less-skilled workers should remain balanced.